Changes functional prediction of ear canal flora in chronic bacterial otitis externa - Duan, Tingting; Li, Zhiqun; Han, Xiaoyong; Hong, Qichao; Yang, Yunan (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveTo investigate ear canal microflora’s structure, composition and function in patients with chronic bacterial otitis externa.MethodsA case-control study design method was used to collect the ear canal secretions from 14 patients with chronic bacterial external otitis (CB group) and 14 healthy controls (H group) treated in the Department of Otolaryngology and Head and Neck Surgery in the First Affiliated Hospital of Hainan Medical University. 16S rRNA high-throughput sequencing technology was used to sequence the ear canal microflora’s V3 V4 region gene amplification products in the participating population. The α diversity of ear canal microflora in 2 groups was analyzed. Based on the weighted Unifrac distance, principal coordinate analysis was performed to compare the β diversity of ear tract microflora between the two groups. The differences in ear microflora at phylum and genus levels were analyzed. PICRUSt2 function prediction and BugBase phenotype prediction were also performed.Resultsα diversity analysis showed that the diversity and richness of auricular microflora in the CB group were significantly lower than those in the H group. β diversity analysis showed that there were some differences between the two groups. At the phylum level, the relative abundance of Bdellovibrionota, Campylobacterota, and WPS-2 in the microbiota of patients in the CB group was significantly lower than that in the H group, and the differences were statistically significant. At the genus level, the relative abundance of Pseudomonas, Acinetobacter, Pelomonas, Sphingomonas, Bradyrhizobium, Brevundimonas, Enhydrobacter, Actinomyces, Paracoccus and Chryseobacterium in the ear canal of Group H is significantly higher than that of Group CB. Functional prediction of PICRUSt2 suggests that amino acid biosynthesis and bacterial microbiota may be related. In BugBase phenotypic prediction, the contribution of aerobic phenotype in group CB was significantly lower than that in group H.ConclusionThe diversity and abundance of the ear canal flora of patients with chronic bacterial otitis externa were significantly lower than those of the healthy population, and their bacterial colony structure was significantly altered. Dysbiosis of the ear canal flora may be an important cause of chronic bacterial otitis externa.